2022
DOI: 10.5694/mja2.51534
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hearing loss in urban Aboriginal infants: the Djaalinj Waakinj cohort study

Abstract: titis media and associated hearing loss are highly prevalent in Indigenous Australian children. 1 Most relevant prevalence studies have been undertaken in rural and remote regions, although most Indigenous children live in urban areas. 2 One prospective cohort study found that hearing loss was frequent in young Aboriginal children in a semi-arid zone of Western Australia, 3 but its prevalence in Aboriginal infants in urban areas has not been investigated. 4 We therefore estimated the prevalence of hearing lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Furthermore, those with evidence of OM at 2 and/or 6 months of age were 3.5 times more likely to have OM at 12 months of age than those with no prior OM. We recently reported that one in three of these infants had moderate hearing loss at 12 months of age 15 . The association between early onset OM and persistent disease at 12 months is consistent with previous studies in remote communities 17 .…”
Section: Discussion and Conclusionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, those with evidence of OM at 2 and/or 6 months of age were 3.5 times more likely to have OM at 12 months of age than those with no prior OM. We recently reported that one in three of these infants had moderate hearing loss at 12 months of age 15 . The association between early onset OM and persistent disease at 12 months is consistent with previous studies in remote communities 17 .…”
Section: Discussion and Conclusionsupporting
confidence: 90%
“…While larger longitudinal studies are needed, our results highlight the feasibility of and need for early ear health assessments in infants living in urban areas, given the generally asymptomatic nature of OM in infancy. Prompt management is then needed to reduce the likelihood of long‐term hearing loss and potential developmental, social, behavioural, educational outcomes and economic consequences 4–6,15 . Twenty of the 125 study participants are known to have had grommets inserted before 3 years of age, a further indication of the disease burden and need for services.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations